Pemilihan Media Promosi STMIK Pelita Nusantara Medan dengan Metode Analytic Network Process (ANP) - Sinaga, Bosker; Hasugian, Penda Sudarto (LPPM UNIKA Santo Thomas Medan, 2019)
Analytic Network Process (ANP) algorithm is used to find optimal alternatives from a set of alternatives with certain criteria. Selection or process is carried out by evaluating promotional media by distributing questionnaires to students to find out the media to be evaluated next by selecting 4 promotional media, determining criteria and sub criteria by distributing questionnaires to the Chairperson of STMIK Pelita Nusantara, Puket III Student and Promotion Section, and The Chairperson of the Promotion, then processes the data using Super Decisions Software 2.4.0. The highest rating results obtained from the analysis and discussion show that the Internet (0.329). from the results of the distributed questionnaire data processing to the management of STMIK Pelita Nusantara Medan, namely the Chairperson, the Third Bouquet and Promotion Section, and the Chairperson of Pelita Nusantara STMIK Promotion, and the application of the Analyst Network Process (ANP) method with the Super Decisions 2.4.0 Application producing cracking the highest media is the Internet (0.329), followed by School Visits (0.274), Radio (0.213), and Banners / Billboards (0.185).